2015
DOI: 10.1007/978-3-319-16522-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adult Hippocampal Neurogenesis in Cognition in Physiology and Disease: Pharmacological Targets and Biomarkers

Abstract: Adult hippocampal neurogenesis is a remarkable form of brain structural plasticity by which new functional neurons are generated from adult neural stem cells/precursors. Although the precise role of this process remains elusive, adult hippocampal neurogenesis is important for learning and memory and it is affected in disease conditions associated with cognitive impairment, depression, and anxiety. Immature neurons in the adult brain exhibit an enhanced structural and synaptic plasticity during their maturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 384 publications
(373 reference statements)
1
38
0
1
Order By: Relevance
“…Mesenchymal stem cells have been demonstrated to secret several factors, BDNF, bFGF, CNTF, FGF-2, GDNF, HGF, IGF, NGF, NT-3, VEGF, to regulate the microenvironment in the brain [33]. We explored neurotropic factors, BDNF, NGF, and NT-3, which were known to be important for neurogenesis [34], learning and memory [35]. We found that hUC-MSCs upregulated the expression of BDNF, NGF, and NT-3 in the hippocampus, and the effects were further enhanced when hUC-MSCs was combined with resveratrol, therefore, hippocampal neurogenesis and cognition were enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells have been demonstrated to secret several factors, BDNF, bFGF, CNTF, FGF-2, GDNF, HGF, IGF, NGF, NT-3, VEGF, to regulate the microenvironment in the brain [33]. We explored neurotropic factors, BDNF, NGF, and NT-3, which were known to be important for neurogenesis [34], learning and memory [35]. We found that hUC-MSCs upregulated the expression of BDNF, NGF, and NT-3 in the hippocampus, and the effects were further enhanced when hUC-MSCs was combined with resveratrol, therefore, hippocampal neurogenesis and cognition were enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of animal studies have implicated adult-born hippocampal neurons, which have different physiological properties than mature neurons, in many non-mutually exclusive roles in brain function, such as formation, spatial memory, pattern separation and the regulation of stress and affective states. Furthermore, in animal models of neurodevelopmental disorders, Alzheimer’s disease, stress and depression, alterations in neurogenesis that correlate with behavioral and cognitive symptoms have been observed and are modulated with pro- or anti-neurogenic stimuli45. Ultimately, the ability to track neurogenesis in longitudinal studies of living human brains will allow researchers to establish the importance of this process in physiology and disease, ultimately impacting the diagnosis and therapy of CNS disorders.…”
mentioning
confidence: 99%
“…Even though the molecular mechanisms underlying this process remain unclear, adult hippocampal neurogenesis plays a significant role in learning and memory formation, and it is affected by environmental changes and disease conditions [Costa et al, 2015]. There are multiple modulators that affect the formation of newborn neurons such as neurotrophic factors, cytokines and chemokines, epigenetic factors, and signaling pathways.…”
Section: Discussionmentioning
confidence: 99%